PENGARUH PANDEMI COVID-19 TERHADAP MOTIVASI BELAJAR MAHASISWA SANTRI SEKOLAH TINGGI ILMU KESEHATAN SURYA GLOBAL YOGYAKARTA - Rofik, Mochamad; Herlambang, Susatyo (LPPM Akademi Manajemen Administrasi Yogyakarta, 2021)
The purpose of this study was to determine student learning motivation during the Covid-19 pandemic. The method used in this study is a quantitative method, with 50 samples. The results of the R2 test in this study were 0.044 or 4.4%. This means that the magnitude of the influence of the Covid-19 pandemic variable on the learning motivation of students at the Surya Global School of Health Sciences (STIKES) of Surya Global Yogyakarta is 4.4%, while the remaining 95.6% (100%-4.4%) must be explained by the following factors: other causative factors. The result of t count shows t count < t table (-1.488 < 1.677); There is an insignificant effect between the Covid-19 pandemic on the learning motivation of students at Surya Global School of Health Sciences (STIKES) Yogyakarta.